PENGARUH EKUITAS MEREK DAN PROMOSI TERHADAP MINAT BELI PRODUK KOSMETIK PT. ORINDO ALAM AYU (ORIFLAME CABANG MEDAN) - LASRIDA SIGALINGGING (LP2MTBM MAKARIOZ, 2021)
The present study is a survey using an associative quantitative approach aimed at analyzing the effect of both brand equityand promotion on the buying interest of comsetic product of PT. Oriindo Alam Ayu (Oriflame Medan). The population of thestudy included all the customers of Orindo Alam Ayu Medan as of 251 people during 2018 and the sampling method usedSlovin formula so that there were 111 samples. The instrument of data collection used a questionnaire and the collecteddata was then analyzed by using a multiple linear regression. The result of the study showed that brand equity partially hada significant effect on buying interest. Promotion partially had a significant effect on buying interest. Brand equity andpromotion simultaneously have a positive and significant effect on buying interest. It is suggested to PT. Orindo Alam AyuMedan to further improve promotion so that buying interest may be maximized. It is also suggested to the employees ofPT. Orindo Alam Ayu Medan to further improve the quality of the brand so that buying interest can be maximized.